2013
DOI: 10.1162/jocn_a_00346
|View full text |Cite
|
Sign up to set email alerts
|

Segregating the Neural Correlates of Physical and Perceived Change in Auditory Input using the Change Deafness Effect

Abstract: Psychophysical experiments show that auditory change detection can be disturbed in situations in which listeners have to monitor complex auditory input. We made use of this change deafness effect to segregate the neural correlates of physical change in auditory input from brain responses related to conscious change perception in an fMRI experiment. Participants listened to two successively presented complex auditory scenes, which consisted of six auditory streams, and had to decide whether scenes were identica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 76 publications
(107 reference statements)
2
7
0
Order By: Relevance
“…Only a portion of the right posterior superior temporal gyrus and the superior temporal sulcus showed consistently higher BOLD responses following both task-relevant and irrelevant pitch changes as compared to changes in sound duration. This rightward lateralization is in good agreement with previous data reporting a righthemispheric dominance for processing pitch information and pitch changes, suggesting that the observed activation may be related to the sensory processing of the changed pitch information in auditory cortex [Patterson et al, 2002;Puschmann et al, 2013;Zatorre and Belin, 2001]. Most studies however reported pitch-induced sensory activity to be localized to more anterior parts of the auditory cortex, in particular to the lateral aspect of Heschl's gyrus and the anterior portion of the planum temporale [Hall and Plack, 2009;Penagos et al, 2004;Puschmann et al, 2010].…”
Section: Feature-related Differences In Early Change Detectionsupporting
confidence: 91%
“…Only a portion of the right posterior superior temporal gyrus and the superior temporal sulcus showed consistently higher BOLD responses following both task-relevant and irrelevant pitch changes as compared to changes in sound duration. This rightward lateralization is in good agreement with previous data reporting a righthemispheric dominance for processing pitch information and pitch changes, suggesting that the observed activation may be related to the sensory processing of the changed pitch information in auditory cortex [Patterson et al, 2002;Puschmann et al, 2013;Zatorre and Belin, 2001]. Most studies however reported pitch-induced sensory activity to be localized to more anterior parts of the auditory cortex, in particular to the lateral aspect of Heschl's gyrus and the anterior portion of the planum temporale [Hall and Plack, 2009;Penagos et al, 2004;Puschmann et al, 2010].…”
Section: Feature-related Differences In Early Change Detectionsupporting
confidence: 91%
“…The average false alarm rate here was somewhat lower than Gregg and Samuel (2008) reported (0.04 vs. 0.10), which resulted in a somewhat higher estimate of average d’ in the present study than the previous study (2.80 vs. 2.22, respectively). Consistent with others (e.g., Puschmann et al, 2013a, 2013b; McAnally et al, 2010), average d’ values across conditions were fairly high, indicating that listeners were quite sensitive to changes in the sound scenes. 1 …”
Section: Resultssupporting
confidence: 87%
“…In the change blindness literature, the influence of response bias is recognized and thus analyses typically report performance based on SDT measures of sensitivity in addition to accuracy measures (e.g., Mitroff et al, 2004). Although SDT approaches have not been broadly applied in the change deafness literature, there are notable examples (e.g., Eramudugolla et al, 2005; Gregg & Samuel, 2008; McAnally et al, 2010; Puschmann et al, 2013a, 2013b) that report evidence of change deafness despite using a bias-free measure of sensitivity. Here, we report measures of accuracy and SDT measures to examine patterns of hits and false alarms as well as a bias-free measure of sensitivity ( d’ ) using an AX (same-different) task.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, an fMRI study on change deafness found greater activity in the anterior cingulate cortex and right insula during successful change detection trials compared with unsuccessful trials. 131 These successful detection trials were also associated with stronger functional connectivity between the right auditory cortex and both the left insula and the left inferior frontal cortex regions, when compared with unsuccessful trials. In contrast, the right superior temporal sulcus showed stronger functional connectivity with the auditory cortex for unsuccessful trials compared with successful trials.…”
Section: Understanding Processing Of Realistic Auditory Scenesmentioning
confidence: 94%